Behavioural responses of freshwater zooplankton vary according to the different alarm signals of their invertebrate predators - Gutierrez, Marìa Florencia (2013)
Single behavioural interactions between two freshwater planktonic crustaceans and invertebrate predators from different zones of the common environment were studied. The planktonic prey organisms were the cladoceran Ceriodaphnia dubia and the copepod Notodiaptomus conifer. The three invertebrate predators were the shrimp Macrobrachium borellii, the crab Trichodactylus borellianus and the larva of the dipteran midge Chaoborus. Feeding experiments were first performed to document the effects of exposure time and prey density on predation. All the selected predators fed on C. dubia and N. conifer, and predation rates were dependent on prey density and exposure time. The ability of microcrustaceans to modify their swimming and avoidance behaviour when faced with cues from each predator was then analysed. The cladoceran was more vulnerable to decapod predation, whereas the prey microcrustaceans were taken equally by the dipteran larvae. The analysis showed that the microcrustaceans detected the presence of at least one invertebrate predator through the predator alarm signals. The cladoceran responded to chemical signals from the three predators but copepods modified their behaviour only in the presence of infochemicals of M. borellii. The different outcomes suggest that macrocrustaceans have different vulnerabilities when faced with the same predator and so have evolved specific and different strategies to reduce invertebrate predation.